Material Culture and (Forced) Migration Materializing the transient - Yi-Neumann, Friedemann; Lauser, Andrea; Fuhse, Antonie; Bräunlein, Peter J. (UCL Press, 2022)
Material Culture and (Forced) Migration argues that materiality is a fundamental dimension of migration. During journeys of migration, people take things with them, or they lose, find and engage things along the way. Movements themselves are framed by objects such as borders, passports, tents, camp infrastructures, boats and mobile phones. This volume brings together chapters that are based on research into a broad range of movements - from the study of forced migration and displacement to the analysis of retirement migration. What ties the chapters together is the perspective of material culture and an understanding of materiality that does not reduce objects to mere symbols. Centring on four interconnected themes - temporality and materiality, methods of object-based migration research, the affective capacities of objects, and the engagement of things in place-making practices - the volume provides a material culture perspective for migration scholars around the globe, representing disciplines such as anthropology, sociology, contemporary archaeology, curatorial studies, history and human geography. The ethnographic nature of the chapters and the focus on everyday objects and practices will appeal to all those interested in the broader conditions and tangible experiences of migration.